2018
DOI: 10.15252/embj.201798452
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput identification of RNA nuclear enrichment sequences

Abstract: In the post‐genomic era, thousands of putative noncoding regulatory regions have been identified, such as enhancers, promoters, long noncoding RNAs (lncRNAs), and a cadre of small peptides. These ever‐growing catalogs require high‐throughput assays to test their functionality at scale. Massively parallel reporter assays have greatly enhanced the understanding of noncoding DNA elements en masse. Here, we present a massively parallel RNA assay (MPRNA) that can assay 10,000 or more RNA segments for RNA‐based func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 47 publications
4
69
0
Order By: Relevance
“…The last piece of evidence which suggests that nuclear export is the default pathway is that when nuclear localized lncRNAs were analyzed, it was observed that they contained nuclear retention elements ( Miyagawa et al, 2012 ; Zhang et al, 2014a ; Lubelsky and Ulitsky, 2018 ; Shukla et al, 2018 ). When these nuclear retention elements were removed or mutated, the altered lncRNAs were exported.…”
Section: What Is the Default Pathway?mentioning
confidence: 99%
“…The last piece of evidence which suggests that nuclear export is the default pathway is that when nuclear localized lncRNAs were analyzed, it was observed that they contained nuclear retention elements ( Miyagawa et al, 2012 ; Zhang et al, 2014a ; Lubelsky and Ulitsky, 2018 ; Shukla et al, 2018 ). When these nuclear retention elements were removed or mutated, the altered lncRNAs were exported.…”
Section: What Is the Default Pathway?mentioning
confidence: 99%
“…Indeed, despite these examples, it has been well-studied that Pol II transcription and the 3′-end alternative processing of the NEAT1 lncRNA act together to modulate paraspeckle morphology and function (Mao et al 2011;Naganuma et al 2012;Hirose et al 2014;Wang et al 2018;Yamazaki et al 2018). Emerging studies have also revealed both cis-and trans-factors are required for the subcellular localization of Pol II-transcribed mRNA-like lincRNAs and functions (Hacisuleyman et al 2014;Zhang et al 2014b;Lubelsky and Ulitsky 2018;Shukla et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs that are only found in the nucleus are classified as nuclear lncRNAs. These lncRNAs contain specific sequences to indicate that they have to be retained in the nucleus [90,91]. Most of the nuclear lncRNAs are regulators of transcription or influence mRNA processing; they can both enhance or silence the transcription of genes, for example, by recruiting transcription factors or by acting as decoy impeding the binding of transcription factors to DNA.…”
Section: Nuclear Lncrnasmentioning
confidence: 99%